Financial Performance Assessment with Cash Flow Analysis Case Study of PT Sinar Mas Agro Resources and Technology Tbk Period 2017-2021 - Puspasari, Dyah; Damayanti, Eva Bening (Journal of Applied Business, Taxation and Economics Research, 2025)
The assessment of financial performance with cash flow analysis at the company in this study aims to determine how the financial performance of PT Sinar Mas Agro Resources and Technology Tbk in the 2017-2021 Period, when measured using the company's cash flow statement. In this study, the authors used a descriptive quantitative approach by looking for information about financial statements without any engineering. The financial statements needed are the Balance Sheet, Profit / Loss Statement, Cash Flow Statement, and CALK for 2017-2021 obtained from the annual report of PT Sumber Mas Agro Resources and Technology Tbk. And the data analysis technique in this study uses cash flow ratio analysis. The results obtained by this study are that the financial performance of PT Sumber Mas Agro Resources and Technology Tbk for the 2017-2021 period assessed from the analysis of the cash flow statement ratio is declared good, because from the results of the calculation of the five cash flow ratios, it states that three ratios have met the standard one (1), namely the capital expenditure ratio, the operating cash flow coverage ratio to interest, and the net profit ratio. Only two ratios do not meet the standard of one (1), namely the operating cash flow ratio and the total debt ratio. From these results, PT Sinar Mas Agro Resources and Technology Tbk is expected to pay more attention to the performance between operating cash flow to the company's current liabilities.